Council Court’s Judgement in the Decision of Sued for Divorce Husband at the Tapaktuan Syar'iyah Court - Nazlianto, Riza (Budapest International Research and Critics University, 2019)
Shari'ah gives the wife the right to complain to the judge gives thalaq to him, even the Shari'ah also requires the judge to grant his wish if found causes that push to gives thalaq to in accordance with what is desired by the wife, while the husband does not want to divorce his wife good road. The aim of this research is to know the divorce case in society Tapaktuan. In compiling this thesis of researchers use qualitative research methods.